Melatonin Influences the Imbalance in Neural Cell Adhesion Molecule (NCAM) Isoforms in Diabetes Mellitus - Kirichenko, S. V.; Nedzvetsky, V. S.; Baydas, G.; Nerush, P. A. (Springer, 2002)
Diabetes mellitus is associated with significant cognitive deficiencies, which develop in a parallel manner with neurophysiological and structural changes in the brain. Intravenous or intraperitoneal injections of a cytotoxic agent influencing the beta cells, streptozotocin (STZ), is most often used to create animal models of diabetes. The pathogenesis of diabetic encephalopathy is not yet understood, but an impairment of spatial learning occurs in association with distinct changes in hippocampal synaptic plasticity. Cell adhesion molecules are good candidates to participate in synaptogenesis on neuronal plasticity. It has been proposed that neural cell adhesion molecule mediates synaptic plasticity during learning and memory formation.
Keywords: melatonin; NCAM isoforms; hippocampus; cortex; diabetes mellitus; streptozotocin; behavioral tests